2014
DOI: 10.6007/ijarbss/v4-i11/1289
|View full text |Cite
|
Sign up to set email alerts
|

Solid Waste Management in Jordan

Abstract: Solid waste became one of the major environmental problems in Jordan, which has been aggravated over the past 15 years by the sharp increase in the volume of waste generated as well as qualitative changes in its composition. The challenges face solid waste management (SWM) in Jordan are numerous. Financial constraints, shortage of proper equipment and limited availability of trained and skilled manpower together with massive and sudden population increases due to several waves of forced migration.In this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Furthermore, annual savings of US$4.65 million will replacement of fuel oil with the generated biogas will achieveannual savings of US$4.65 million. Also, studies concerning the energy production content of municipal solid waste in Jordan was conducted and it accounted for 6% of the annual imported oil consumption of the country and may result in an annual saving of US$24 million in case of the utilization (Aljaradin, 2014). In table 2 the changing in electrical energy supply in Jordan for the years, 2004-2007 is presented, the growth rate in biogas production for electricity generation is large, but the proportion of the total electrical energy supply from an-fossil sources is small.…”
Section: The Problem Of Waste Managementmentioning
confidence: 99%
“…Furthermore, annual savings of US$4.65 million will replacement of fuel oil with the generated biogas will achieveannual savings of US$4.65 million. Also, studies concerning the energy production content of municipal solid waste in Jordan was conducted and it accounted for 6% of the annual imported oil consumption of the country and may result in an annual saving of US$24 million in case of the utilization (Aljaradin, 2014). In table 2 the changing in electrical energy supply in Jordan for the years, 2004-2007 is presented, the growth rate in biogas production for electricity generation is large, but the proportion of the total electrical energy supply from an-fossil sources is small.…”
Section: The Problem Of Waste Managementmentioning
confidence: 99%
“…The northern area provides around 780 tons per day, the center region approximately 2620 tons per day, and the southern part around 400 tons per day. Aljaradin [ 34 ] discussed the challenges Jordan faces regarding solid waste management (SWM), including financial constraints, a lack of proper equipment, a scarcity of trained and skilled human resources, and a massive and sudden population, increases due to several waves of forced migration. Furthermore, their analysis also includes suggestions and recommendations for the development of the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more attention has been paid to SW management in Jordan, focusing on recycling, recovery, and reuse. Therefore, researchers have been funded and conducted studies concerning energy and material recovery from Evaluating the In-site Sorting of Solid Waste in Selected Educational Institutions -A Pilot Study Husam Al-Hamaiedeh 1* , Enam Al-Rafiaha 1 , Omar Al-Khashman 2 , Osama Mohawesh 3 , Ali El Hanandeh 4 SW in Jordan [Aljbour et al, 2021;Al-Hajaya et al, 2021;Al Nawaiseh et al, 2021]. Jaradat and Al-Khashman (2013) evaluated the potential recovery of materials from municipal SW (MSW) in Jordan, Ma'an; they concluded that municipal SW management is still facing many challenges due to insufficient data concerning its quality and characteristics.…”
Section: Introductionmentioning
confidence: 99%